2002
DOI: 10.1046/j.1365-2265.2002.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin in human pituitary adenomas: frequency and clinical significance

Abstract: Galanin is present in normal and tumorous human pituitaries. In addition, GAL colocalizes exclusively in corticotrophs of normal pituitaries and is coexpressed almost exclusively in corticotrophs from functioning and nonfunctioning tumours. The finding that corticotroph adenomas can function irrespective of the presence of GAL suggests that GAL may not play a pathophysiological role in Cushing's disease. However, the better surgical outcome observed in patients with Cushing's disease who had tumours positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Human pheochromocytoma was the first tumor in which galanin was identified (Bauer et al, 1986c;Hacker et al, 1988), and later galanin-like immunoreactivity was detected in other neuroendocrine tumors, including human pituitary adenoma (Bauer et al, 1986c;Hacker et al, 1988). Subsequently, galanin-like immunoreactivity was detected in human pituitary adenoma particularly associated with adrenocorticotrophic hormone-secreting cells (Hulting et al, 1989;Vrontakis et al, 1990;Bennet et al, 1991;Hsu et al, 1991;Sano et al, 1991;Leung et al, 2002;Grenback et al, 2004) and in gangliocytoma (Sano et al, 1991;Felix et al, 1994), paraganglioma (Fried et al, 1994;Tadros et al, 2003), and neuroblastoma (Tuechler et al, 1998). Alarin was subsequently detected in differentiated neuroblastoma cells (Santic Galanin Family Peptides and Receptors et al, 2006) and was recently detected in a variety of human CNS tumors and suggested to be a diagnostic marker for ependymoma to differentiate them from other gliomas (Eberhard et al, 2013).…”
Section: Cancermentioning
confidence: 99%
“…Human pheochromocytoma was the first tumor in which galanin was identified (Bauer et al, 1986c;Hacker et al, 1988), and later galanin-like immunoreactivity was detected in other neuroendocrine tumors, including human pituitary adenoma (Bauer et al, 1986c;Hacker et al, 1988). Subsequently, galanin-like immunoreactivity was detected in human pituitary adenoma particularly associated with adrenocorticotrophic hormone-secreting cells (Hulting et al, 1989;Vrontakis et al, 1990;Bennet et al, 1991;Hsu et al, 1991;Sano et al, 1991;Leung et al, 2002;Grenback et al, 2004) and in gangliocytoma (Sano et al, 1991;Felix et al, 1994), paraganglioma (Fried et al, 1994;Tadros et al, 2003), and neuroblastoma (Tuechler et al, 1998). Alarin was subsequently detected in differentiated neuroblastoma cells (Santic Galanin Family Peptides and Receptors et al, 2006) and was recently detected in a variety of human CNS tumors and suggested to be a diagnostic marker for ependymoma to differentiate them from other gliomas (Eberhard et al, 2013).…”
Section: Cancermentioning
confidence: 99%
“…Local galanin release has been postulated in other systems, such as tumors. In particular, it has been proposed that galanin is secreted from neuroblastomas (Tuechler et al,1998; Perel et al,2002) and pituitary adenomas (Invitti et al,1999; Leung et al,2002; Grenback et al,2004) and acts on galanin autoreceptors. This set of data strengthens the hypothesis of paracrine/autocrine actions of galanin, which is consistent with its somatodendritic release in differentiated neuronal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed that in many pituitary adenomas galanin-positive cells were almost exclusively corticotrophs (69), although some ACTH-secreting adenomas did not express galanin (70). Direct evidence is lacking, but some observations may suggest that galanin is involved in the development of pituitary-cell hyperplasia and tumorigenesis.…”
Section: Involvement Of Galanin In the Pathophysiology Of The Hpa Axismentioning
confidence: 97%
“…Abundant evidence indicates that galanin is expressed in the mammalian anterior pituitary as mRNA and protein (56)(57)(58)(59)(60)(61). In situ hybridization and ICC showed that galanin-positive cells are: i) in female rats predominantly lactotrophs (62)(63)(64)(65), where galanin is co-localized with prolactin in the secretory granules (66); ii) in male rats mainly somatotrophs, thyreotrophs (61) and corticotrophs (65,67); iii) in adult male monkeys thyreotrophs and gonadotrophs (68); and iv) in normal human pituitary and pituitary adenomas almost exclusively corticotrophs (69,70). Galanin-positive nerve fibers were found in the dog, monkey and human anterior pituitary (71,72).…”
Section: Expression Of Galanin and Its Receptors In The Hpa Axismentioning
confidence: 99%